Evaluasi Kinerja Heat Exchanger 02 Di Pusat Pengembangan Sumber Daya Manusia (PPSDM) Minyak Dan Gas Bumi Cepu - Fadiya Ananda Dardiri; Dyan Hatining Ayu Sudarni (CV. Multi Kreasi Media, 2023)
Transfer from high temperature to low temperature to have the same temperature, either directly (without separation) or indirectly (the separation). Heat exchanger is a heat exchanger that is useful for changing the temperature and phase of a type of fluid. Therefore, it is necessary to evaluate the performance of heat exchangers. This performance evaluation greatly affects the performen of the heat exchanger. Parameters measured to know performen is the determination of the value of Rd, presure drop, and efficiency of the tool. While the necessary data is taken by direct observation. The purpose of the evaluation was to determine the current performance of the heat exchanger, especially HE-02 at the PPSDM Migas CEPU refinery. From the results of calculations that have been done obtained the results of performance evaluation of heat exchanger 02 is the value of effesiensi 95.275%, the value of faouling factor (Rd) is 0.417 , the pressure drop for the shell is 0.046 Psi and the value of the pressure droop on the tube is 0.005 Psi..